Model Pengembangan Sport Tourism Melalui Video Edukatif Atraksi Mepantigan di Batubulan, Bali - Sang Made Wahyu Rusmayana; Ida Bagus Putra Yadnya; Agus Made Yoga Iswara (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Sport tourism makes a significant contribution to the economy by increasing tourist participation and strengthening the appeal of tourist destinations. The Indonesian government’s policies in supporting culture-based sport tourism, such as Mepantigan, are reflected in various regulations and strategic programs. One of the key policies is the development of culture-based tourism as stated in the National Tourism Development Master Plan (RIPPN) 2011–2025, in which the government is committed to promoting and preserving local culture as part of tourism attractions. This study aims to design a sport tourism development model through educational videos of the Mepantigan attraction in Batubulan, Bali. Mepantigan is a traditional Balinese martial art that holds great potential as a culture- and sport-based tourism attraction. However, promotion of this attraction on digital platforms remains limited, with content that is not yet educational and relies only on a single social media channel. This study employs a qualitative method using in-depth interviews, participatory observation, documentation study, and focus group discussions. The results show that educational videos using cinematographic approaches and the AIDAS strategy are able to enhance the appeal of Mepantigan as part of sport tourism. The recommended innovative digital platform model includes the use of YouTube and TikTok to reach a wider audience as well as the application of visual techniques such as slow motion to highlight the cultural values and philosophy of Mepantigan. This research is expected to serve as a reference for the development of culture-based sport tourism promotion through digital media. The appropriate development strategy is a growth strategy through the optimization of multichannel digital media (YouTube, Instagram, TikTok) using educational video instruments as the main promotional tool, while simultaneously strengthening Mepantigan branding as an innovative sport tourism attraction in Bali.